Perinatal ethanol exposure affects cell populations in adult dorsal hippocampal neurogenic niche - Villalba, Nerina (2023)
Neurodevelopment is highly affected by perinatal ethanol exposure (PEE). In the adult brain, neurogenesis takes place in the dentate gyrus (DG) of the hippocampus and in the subventricular zone. This work aimed to analyze the effect of PEE on the cellular types involved in adult dorsal hippocampal neurogenesis phases using a murine model. For this purpose, primiparous female CD1 mice consumed only ethanol 6% v/v from 20 days prior to mating and along pregnancy and lactation to ensure that the pups were exposed to ethanol throughout pre- and early postnatal development. After weaning, pups had no further contact with ethanol. Cell types of the adult male dorsal DG were studied by immunofluorescence. A lower percentage of type 1 cells and immature neurons and a higher percentage of type 2 cells were observed in PEE animals. This decrease in type 1 cells suggests that PEE reduces the population of remnant progenitors of the dorsal DG present in adulthood. The increase in type 2 cells and the decrease in immature neurons indicate that, during neurodevelopment, ethanol alters the capacity of neuroblasts to become neurons in the adult neurogenic niche. These results suggest that pathways implicated in cell determination are affected by PEE and remain affected in adulthood.